Motif Penggunaan Aplikasi Tik Tok di Kota Semarang - Nuzuli, Ahmad Khairul; Natalia, Wahyu Kristian (School of Communication - Atma Jaya Catholic University of Indonesia, 2021)
Initially the use of Tik Tok received negative views. However, in 2019 Tik Tok managed to beat Facebook and Instagram in popularity. The purpose of this research is to find out the motives of Tik Tok users in creating and sharing their music videos. The theoretical basis used is Uses and Gratification and Media Usage Motives, which assume that media users are active and deliberately determine their motives in using and consuming media. This research is quantitative research with a descriptive approach. The number of samples in this study was 100 people. With the criteria of the people of Semarang City, having the Tik Tok application on a smartphone, having made and uploading at least 5 videos using the Tik Tok application. The results of the study show that there are four main motives in the use of Tik Tok social media, namely: 1) information motives; 2) personal identity; 3) social integration and interaction; 4) and entertainment. The most dominant motive is integration and social interaction.